2009
DOI: 10.1161/circheartfailure.108.812099
|View full text |Cite
|
Sign up to set email alerts
|

Control by Circulating Factors of Mitochondrial Function and Transcription Cascade in Heart Failure

Abstract: Background-Evidence is emerging to support the concept that the failing heart is "energy depleted" and that defects in energy metabolism are important determinants in the development and the progression of the disease. We have shown previously that depressed mitochondrial function in cardiac and skeletal muscles in chronic heart failure is linked to decreased expression of the gene encoding transcriptional proliferator-activated receptor-␥ coactivator-1␣, the inducible regulator of mitochondrial biogenesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 52 publications
7
49
0
Order By: Relevance
“…Indeed, doxorubicin treatment also altered mitochondria more severely in males, as evidenced by the downregulation of gene expression of mitochondrial 39 PGC-1α and its targets are downregulated in different experimental models of heart failure and in patients. 40,41 The same was found in daunorubicin-treated male rabbits. 14 In the present study, PGC-1β seemed a relevant target of doxorubicin in males because its downregulation is also observed at the onset of cardiac toxicity.…”
Section: Discussionsupporting
confidence: 62%
“…Indeed, doxorubicin treatment also altered mitochondria more severely in males, as evidenced by the downregulation of gene expression of mitochondrial 39 PGC-1α and its targets are downregulated in different experimental models of heart failure and in patients. 40,41 The same was found in daunorubicin-treated male rabbits. 14 In the present study, PGC-1β seemed a relevant target of doxorubicin in males because its downregulation is also observed at the onset of cardiac toxicity.…”
Section: Discussionsupporting
confidence: 62%
“…Importantly, PGC-1␣ is lower in the failing heart. The report by Garnier et al, 4 in this issue shows that ET-1 and angiotensin II downregulate whereas aldosterone and isoprenaline upregulate PGC-1␣ expression in ventricular myocytes. NRF indicates nuclear respiratory factors; ERR, estrogen receptors; PPAR, peroxisome proliferator-activated receptors; RXR, retinoid receptors.…”
Section: Rat Ventricular Myocytesmentioning
confidence: 80%
“…A study by Scheubel et al, 12 in which mitochondrial enzyme activities were found to be unchanged in human failing hearts, normalized activities to CS activity. Importantly, the data presented by Garnier et al 4 show that CS, a good marker of mitochondrial mass, also decreased. Normalizing cyclooxygenase and CK activities to CS activity in the Garnier et al 4 study would show the same apparently misleading result.…”
Section: Human Myocardiummentioning
confidence: 86%
“…Among several targets for redox-dependent Ang-II actions in skeletal muscle, modulation of insulin/insulin-like growth factor (IGF) pathway (Brink et al, 2001) and mitochondrial biogenesis (Garnier et al, 2009;Mitsuishi et al, 2009) seem to play an important role. For example Ang-II infusion into mice resulted in a down-regulation of circulating IGF-1, and the local over expression of IGF-1 prevented Ang-II mediated proteolysis and skeletal muscle apoptosis (Song et al, 2005).…”
Section: Introductionmentioning
confidence: 99%